PENERAPAN PROBLEM BASED LEARNING (PBL) PADA PEMBELAJARAN SEJARAH UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS DAN HASIL BELAJAR SISWA KELAS XII IPS 1 SMA NEGERI 1 WURYANTORO KABUPATEN WONOGIRI TAHUN 2015/2016 - Brahmowisang, Ambrusius Kuncoro; Sariyatun, S.; Agung S., Leo (Sebelas Maret University (UNS), 2016)
Model of problem based learning (PBL) is a learning approach where students are exposed to a problem that then through the problem solving the students learn the abilities through inquiry and thought so it can make the student become independent in learning and solving problems. This research aims to determine whether the application of the model of problem based learning (PBL) in the teaching of history can improve critical thinking skills and learning outcomes of history lesson of students in the third grade of social class 1 of State Senior High School 1 Wuryantoro Wonogiri,AcademicÂ Year 2015/2016. This study is a Class Action Research (Classroom Action Research) consists of three cycles with the stages of planning, implementation, observation and reflection. This research subject is the third grade students of social class1 State Senior High School 1 Wuryantoro Wonogiri involving 25 students. Data collection technique used tests, observation, interviews, documentation, and questionnaires. Data analysis technique used descriptive qualitative analysis techniques. The results of the research showed based on test results, critical thinking skills students acquired in the first cycle with an average value of 73.40 and classical passing grade 64%, the second cycle with an average value of 77.20 and classical passing grade 80%, and the cycle III with an average of 80.60 and classical passing grade 88%. While the study results obtained by students in the first cycle with an average value of 73.20 and classical passing grade 68%, the second cycle with an average value of 76.60 and classical passing grade 76%, the third cycle with the average value at 80.20 with the achievement of 84% passing grade . The application of the model problem based learning (PBL) can improve critical thinking skills and student learning outcomes.Â